Comparative Study of the Budgeting Process Reforms Within Two International Accounting Organisations: Malaysia and Australia Perspectives - Wong, Edward Sek Khin (American-Eurasian Network for Scientific Information, Jordan, 2010)
This paper discusses the budgeting process and the extent of organisational political influence within the budgeting process in two different accounting firms. It identifies the role of organisational politics on the relationship between managerial roles and the budgeting process. It discusses the activities involved in the budgeting process which includes the budgetary participants, budgetary communications, budgetary controls and budgetary evaluation. It also explores the characteristics of managerial roles including interpersonal roles, information roles and decisional roles. In this paper, two accounting firms are used here; one an Australian international accounting firm and the other a Malaysian international accounting firm, called Austral and Malaya respectively, and both are examined to determined the establishing an operating and organisational budget. This paper begins by examining the processes seeking the basis of the controls used, and then by examining the behaviour and the information flows that accompany the new digital information systems that are being put into effect. Initially the paper describes how a company’s budgetary control analysis was used to identify organisation #Malaya’s and # Austral’s budgetary processes. It will then further focused on the framework of behavioural research towards comparing and investigating the information flows of the two Accounting firms in the new digital economy.